The influence of perceived organizational support and work stress on counterproductive behavior in an Islamic economic perspective (study on Central Lampung employees) / Salsabiila Nur Aziizah, A. Zuliansyah and Weny Rosilawati - Nur Aziizah, Salsabiila; Zuliansyah, A.; Rosilawati, Weny (Universiti Teknologi Mara Selangor, 2023)
This thesis aims to determine the influence of perceived organizational support and work stress on counterproductive behavior in an Islamic economic perspective (Study on Central Lampung Employees). Some of the reasons behind this research are because based on the research that has been carried out, that it gets a number of employees who experience work stress, it can be caused by the absence of bonuses given, or jobdesc that does not match their expertise. So that it shows the existence of deviant behavior carried out by employees in the company with various types such as: returning home faster and damaging existing facilities at the company, leaving late, and working unprofessionally. The research method used in this study is the quantitative method. The population used in this study was all employees in Central Lampung. Researchers chose the probability sample type, which is a simple random sampling method with a total sample of 98 people. Next is to analyze the data using the Likert scale with the method used is Partial Least Square (PLS) technique.